(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2025)
Why do some governments resort to providing concessions to dissident challenges whereas other governments resist giving in to their demands? Political unrest occurs throughout the world regardless of government type; however, some governments concede to concessions while others remain steadfastly against acquiescence. Prior literature provide significant understanding on state repression but less progress has been produced on when regimes give in to dissident demands. To provide a theoretical explanation, I argue that the ability of certain authoritarian regimes to survive after reforms lead to institutional change and the perceived threat of the political unrest are the key concepts that influences the decision of the regime to provide concessions or resist any form of change. Using the NAVCO dataset, I use a direct effects model to represent a nonviolent protest campaign and an interactions model to simulate a violent dissident challenge. I find that regimes such as single party and military regimes are more likely to provide concessions to violent campaigns whereas monarchies and personalist regimes are more likely to give in to reforms if the campaigns remain nonviolent.